Prolonged Stabilization of Amyotrophic Lateral Sclerosis (ALS) with a Specially Fermented Soy Product (FSWW08): Case Report and Discussion - Goslin, Kimberley; Schindler, Adolf E.; Rohr, Uwe D. (Journal of Nutritional Therapeutics, 2013)
Amyotrophic lateral sclerosis (ALS) is typically characterized by adult-onset degeneration of the upper and lower motor neurons in mostly male patients, and is usually fatal within 2 to 5 years and is by definition a progressive disease. Only one drug, riluzole, has been approved to treat ALS, which typically provides only a gain of survival of a few months. The exact etiology of ALS isn’t known. However most researchers suggest, that ALS increases inflammation and increases cellular stress so that arriving stem cells and local stem cells cannot differentiate into functional nerve cells: ALS shares on a genetic level many similarities with cancer resistance and supports the view that tissue repair and cancer are related. Deteriorating general immunity in nerve cells causes dementia, mental stress, and anxiety. A fermented soy formulation (FSWW08) has been shown to improve local and general immunity in cancer patients and reduces stress on the molecular as well as a clinical level: FSWW08 improved on the genetic molecular level MAP-kinase, c-Jun, and NF-kB, which are impaired in ALS patients. A 50 year old man diagnosed two years ago with ALS in the neck was given one month later over a two year period standard therapy, standard physical care, riluzole anti-inflammatory drugs, oxybutynin for urge incontinence, and additionally FSWW08. Three month before being diagnosed with ALS; the patient suffered from severe mood swings (anxiety disorders but not depression), which were treated by a psychiatrist. The patient complained about severe sleeping disorders at that time. Improvement of mental and physical well-being of FSWW08 was documented by two questionnaires specifically developed for ALS (Amyotrophic Lateral Sclerosis-Frontotemporal Dementia-Questionnaire [ALS-FTD-Q]) and a quality of life questionnaire from the ESQR questionnaires. The progress of local muscle impairment in the neck, which caused the disease, was stopped after 2 month of consumption of FSWW08, as well as breathing being stabilized at a low, but stable levels above the defined level for obstructive disease. Strong on/off fluctuations of ALS symptoms were observed and documented with the consumption of FSWW08, standard medication was continued and had no effect on on/off motor functions of ALS. When the consumption of the FSWW08 was stopped motor dysfunctions of the arms reappeared within two weeks and the patient lost his ability to speak. When consumption of FSWW08 was resumed the disturbances disappeared within 7 days. Additionally it was observed that immune disturbances, hay fever and usual infections during winter, were completely eliminated. Under FSWW08, mental stress and anxiety was reduced, accompanied by a normal sleeping pattern at night and increased energy levels, which caused increased physical activity. Patient reported improved breathing, documented by stable FVW. The patient exhibited a normalization of blood pressure (from pre diagnosed ALS and no consumption of FSWW08, similarly in the off phase, when FSWW08 was not taken) from 170/100 mm HG to 120/80 mm HG under FSWW08 consumption) within seven days, blood lipids were normalized (cholesterol, triglycerides, HDL, LDL). It is reported in the literature that unfavorable blood lipids are related to severity of ALS in Japanese and Western patients. This is the first time stabilization of ALS has been observed accompanied by improvements in blood lipids in patients. This single report corroborates studies conducted with FSWW08 in other diseases including cancer, severe mental diseases (PTSD and Schizophrenia) and severe virus infections. The FDA has granted a general unspecific Health Claim that soy improves blood lipids like cholesterol and triglycerides. This is the first time a fermented soy formulation, FSWW08, has prevent progression of ALS over a two years period and normalized blood lipids. The special fermentation of FSWW08 causes an increase in immunity, cellular stress reduction and blood lipids. Larger clinical trials in ALS patients with FSWW08 are now warranted to investigating whether these results can be confirmed, and whether FSWW08 increases survival, as well as whether blood lipids are a prognostic marker of ALS.